1977
DOI: 10.1136/jech.31.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Bias resulting from missing information: some epidemiological findings.

Abstract: sumUmARY The biases resulting from missing information were examined in three psychiatric epidemiological studies. In each study, cases with missing information could be compared with the main sample because data were available from several sources or at several points in time through a longitudinal study. In almost all instances, cases with missing data differed systematically in terms of variables crucial to the questions being studied. In general, they tended to include a higher proportion with problems of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 14 publications
(19 reference statements)
1
32
1
1
Order By: Relevance
“…Although epidemiological samples have the advantage of limiting referral biases, our response rate was less than optimal, partially reflecting cultural attitudes towards issues of mental health in children. Some authors have suggested that a low response rate (Cox et al 1977) may reflect exclusion of the most severe cases; thus, the results of analyses addressing the psychometric and causal architecture of mental disorders in nonclinical samples do not necessarily apply to clinical populations. Moreover, since this is a general population sample, it could be argued that the information yielded by this design does not necessarily apply to the more severe cases of children with clumsiness, or autistic traits.…”
Section: Discussionmentioning
confidence: 97%
“…Although epidemiological samples have the advantage of limiting referral biases, our response rate was less than optimal, partially reflecting cultural attitudes towards issues of mental health in children. Some authors have suggested that a low response rate (Cox et al 1977) may reflect exclusion of the most severe cases; thus, the results of analyses addressing the psychometric and causal architecture of mental disorders in nonclinical samples do not necessarily apply to clinical populations. Moreover, since this is a general population sample, it could be argued that the information yielded by this design does not necessarily apply to the more severe cases of children with clumsiness, or autistic traits.…”
Section: Discussionmentioning
confidence: 97%
“…As Cox et al (1977) point out, the missing cases should also be assessed with regard to the variables central to the item of interest and not only in terms of demographic background. In this series, the missing subjects did not differ from the attendants in terms of such determinants as malformations or Apgar scores at 5 or 15 min, but there was a slight overrepresentation of children reported as having had episodes of otitis media among the attendants.…”
Section: Discussionmentioning
confidence: 99%
“…Cox et al (1977) found that at a rate of noncompliance of 8.4%, children of nonrespondent parents show more psychiatric disorders, but do not differ from the participants as regards IQ. A possible explanation for this discrepancy are the different rates of noncompliance and the fact our data suggests that the noncompliants have a tendency to dissimulate (a higher share of pupils repeating a class in the noncompliant group and a tendency to show more symptoms).…”
Section: Problemmentioning
confidence: 94%